Inclination Of Local Government Employees Towards Organizational Citizenship Behaviour: Is It A Must ? - Rashidah, Mohamad Ibrahim; Bahyah, Abdul Halim; Wan Abd Aziz, Wan Mohd Amin (2017)
Local government is ranked lowest in the three-tier Malaysian government behind federal government and state government. Three levels of hierarchy existed in local government structure specifically city council, municipal council and district council. Being the government’s lowest tier and a non-profit organisation, it plays a crucial role as the manager of urban environment to drive economic growth and development of a district and its residents. Since local government is the closest to the community and provides numerous services for the betterment of the living conditions of its residents, it has been constantly under the watchful eyes of the public. Local government has received many complaints as the issues of inefficiency of service quality and delivery has yet to meet the expectations of the public as evidenced from statistics from Public Complaint Bureau (PCB). Thus, in responding to PCB statistics and lack in-depth research on local government, the objective of this study is to ascertain whether dimensions under organizational citizenship behaviour (OCB) namely altruism, courtesy, sportsmanship, civic virtue and conscientiousness are preconditions for local governments’ employees to portray towards reducing public complaints. Data from 493 respondents working in various categories of local governments throughout Peninsular Malaysia were collected through a structured questionnaire using proportioned stratified sampling procedure. Results indicated that majority of the respondents agreed on statements under OCB dimensions with recorded means of between 3.85 to 4.06 based on five-point Likert scale. Descriptive analysis for each item under OCB dimensions were examined and analysed. By creating and sustaining the occurrence of these OCB behaviours, the mandated objective in gaining public trust towards local governments’ efficiency and competency can be achieved since it is a low cost vehicle in influencing organizational effectiveness